2012
DOI: 10.1242/dev.078220
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Bmp4 signaling by the zinc-finger repressors Osr1 and Osr2 is required for Wnt/β-catenin-mediated lung specification in Xenopus

Abstract: SUMMARYEmbryonic development of the respiratory system is regulated by a series of mesenchymal-epithelial interactions that are only partially understood. Mesenchymal FGF and Wnt2/Wnt2b signaling are implicated in specification of mammalian pulmonary progenitors from the ventral foregut endoderm, but their epistatic relationship and downstream targets are largely unknown. In addition, how wnt2 and wnt2b are regulated in the developing foregut mesenchyme is unknown. We show that the Odd-skippedrelated (Osr) zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 64 publications
6
50
0
Order By: Relevance
“…Thus, Wnt ligands may affect PTK7 dynamics in migrating neural crest cells. For example, Wnt2b, which we have shown leads to internalization of PTK7 and colocalizes with PTK7 in intracellular vesicles, is expressed in the Xenopus branchial arches at the time of neural crest migration (Rankin et al, 2012). Neural crest cells also provide an explanation for the relevance of the inhibition of canonical Wnt signaling by PTK7.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, Wnt ligands may affect PTK7 dynamics in migrating neural crest cells. For example, Wnt2b, which we have shown leads to internalization of PTK7 and colocalizes with PTK7 in intracellular vesicles, is expressed in the Xenopus branchial arches at the time of neural crest migration (Rankin et al, 2012). Neural crest cells also provide an explanation for the relevance of the inhibition of canonical Wnt signaling by PTK7.…”
Section: Discussionmentioning
confidence: 76%
“…Analyses of Osr1 −/− mutant mice have shown that Osr1 is required for heart and kidney development (15,16), whereas Osr2 −/− mutant mice exhibit cleft palate and supernumerary tooth formation (17,18). Osr1 and Osr2 have also been shown to regulate kidney and foregut development in Xenopus (14,19). In addition, Osr1 and Osr2 have been shown to function partially redundantly in regulating synovial joint formation during limb skeleton development in mice (20).…”
mentioning
confidence: 99%
“…Some but not all studies have demonstrated that high concentrations of FGF2 increase NKX2-1 expression in differentiating hESC [9,10,15]. Mou et al, found that BMP4 induces NKX2-1 expression in differentiating human induced pluripotent stem cells [16], but Rankin et al found that suppression of BMP4 signaling is required for wnt/beta-catenin-mediated lung specification in Xenopus [17]. Thus, as is true for in vivo development of pulmonary epithelium from definitive endoderm (DE), the signals/growth factors that support specification of m/hESC-derived DE to the pulmonary lineage are not yet understood.…”
mentioning
confidence: 99%